Method for producing spherical alumina particle dispersion, spherical alumina particle dispersion for viewing angle-improving optical film, coating film-forming resin composition for viewing angle-improving optical film, and viewing angle-improving optical film
Patent Information
- Application Number
- JP2021070447
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-24
- Filing Date
- 2021-04-19
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2041-04-19
AI Technical Summary
【0017】 本発明によれば、液晶パネルの表面に設けられる光散乱層の視野角特性を改善する技術を提供することができる。
Smart Images

Figure 0007651092000004 
Figure 0007651092000005 
Figure 0007651092000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a spherical alumina particle dispersion, a spherical alumina particle dispersion for a viewing angle-improving optical film, a coating-forming resin composition for a viewing angle-improving optical film, and a viewing angle-improving optical film. [Background technology]
[0002] Liquid crystal display devices have been widely used in recent years as display devices for televisions, mobile terminals, and the like. However, it is known that liquid crystal display devices suffer from grayscale inversion, color shift, and reduced contrast ratio when viewed from an oblique direction. Known solutions to this problem include (1) a method of arranging a retardation film between the liquid crystal panel and a polarizing plate of the liquid crystal display device, and (2) a method of arranging a light scattering layer on the surface of the liquid crystal panel (e.g., Patent Document 1). Of these, method (2) is considered to be more effective at improving viewing angle characteristics than method (1). However, the current situation is that method (2) has not yet been able to sufficiently improve viewing angle characteristics. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2010 / 143552 Summary of the Invention [Problem to be solved by the invention]
[0004] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a technique capable of improving the viewing angle characteristics of a light scattering layer provided on the surface of a liquid crystal panel. [Means for solving the problem]
[0005] The present inventors have studied how to improve the viewing angle characteristics of a light scattering layer disposed on the surface of a liquid crystal panel, as in the above-mentioned method (2). A light scattering layer is generally made of a film in which a light scattering agent that scatters light from a backlight is dispersed in a polymer that can transmit the light. Therefore, in order to improve the viewing angle characteristics, that is, to widen the viewing angle, the inventors came up with the idea of ensuring the transmittance of light from the backlight and improving the viewing angle by scattering the light better than before with a light scattering agent. Then, after intensive research, the inventors came up with the idea that in order to realize this, it is effective to reduce the particle size of the light scattering agent and disperse it uniformly, but it was found that if there are many amorphous particles when dispersing the fine particles that serve as the light scattering agent, Rayleigh scattering occurs in the light scattering layer, and light of a specific wavelength (especially a wavelength of 900 nm) is emphasized.
[0006] Further investigations have revealed that, when dispersing specific particles serving as light scattering agents, by performing a dispersion process using beads of a specific size, it is possible to suppress the generation of amorphous fine particles and to substantially constitute spherical fine particles, and as a result, it is possible to suppress the occurrence of Rayleigh scattering in the light scattering layer.In addition, it has been found that, by using a specific dispersant, it is possible to suppress the aggregation of specific fine particles serving as light scattering agents, and as a result, it is possible to ensure uniform dispersion of the light scattering agent in the light scattering layer.In other words, it has been found that, by making the fine particles serving as light scattering agents substantially spherical and ensuring the dispersibility of these spherical fine particles in the light scattering layer, it is possible to suppress Rayleigh scattering and at the same time improve the light scattering effect compared to conventional methods, and form a light scattering layer with improved viewing angle characteristics.
[0007] The first aspect of the present invention relates to a method for producing a spherical alumina particle dispersion containing spherical alumina particles, a dispersant and a solvent, the method comprising the steps of dispersing raw alumina particles, which are the raw material for the spherical alumina particles, together with beads having an average particle diameter of less than 0.10 mm, in a liquid containing the raw material alumina particles, the dispersant containing at least one selected from a nonionic dispersant and a cationic dispersant, and the solvent, to disperse the raw alumina particles so that the spherical alumina particles are substantially composed of spherical alumina particles having an average particle diameter of 1 to 10 μm.
[0008] In an embodiment of the present invention, the dispersant may include a nonionic dispersant and a cationic dispersant. The cationic dispersant may be an amine-type polymer dispersant.
[0009] In an embodiment of the present invention, the raw alumina particles may have an average particle size of 1 to 10 μm.
[0010] The second aspect of the present invention relates to a method for producing a coating forming composition, comprising: a spherical alumina particle dispersion preparation step in which a liquid containing raw alumina particles, which are the raw material for the spherical alumina particles, a dispersant containing at least one selected from a nonionic dispersant and a cationic dispersant, and a solvent, is dispersed together with beads with an average particle diameter of less than 0.10 mm to disperse the raw alumina particles so that the spherical alumina particles are substantially composed of spherical alumina particles having an average particle diameter of 1 to 10 μm; and a coating forming composition preparation step in which a coating forming component is added to the spherical alumina particle dispersion obtained in the spherical alumina particle dispersion preparation step, and the mixture is stirred.
[0011] The third aspect of the present invention relates to a method for producing a cured film, comprising: a spherical alumina particle dispersion preparation step in which a liquid containing raw alumina particles, which are the raw material for the spherical alumina particles, a dispersant containing at least one selected from a nonionic dispersant and a cationic dispersant, and a solvent is dispersed together with beads with an average particle diameter of less than 0.10 mm to disperse the raw alumina particles so that the spherical alumina particles are substantially composed of spherical alumina particles having an average particle diameter of 1 to 10 μm; a coating film-forming composition preparation step in which a coating film-forming component is added to the spherical alumina particle dispersion obtained in the spherical alumina particle dispersion preparation step and mixed; and a cured film formation step in which the coating film-forming composition obtained in the coating film-forming composition preparation step is applied to a substrate surface to form a coating film, and then cured to form a cured film.
[0012] In an embodiment of the present invention, the cured film may be for a viewing angle improving optical film.
[0013] The fourth aspect of the present invention relates to a spherical alumina particle dispersion for a viewing angle improving optical film, the dispersion containing spherical alumina particles substantially composed of spherical alumina particles having an average particle size of 1 to 10 μm, a dispersant containing at least one selected from a nonionic dispersant and a cationic dispersant, and a solvent. In an embodiment of the present invention, the dispersant may contain a nonionic dispersant and a cationic dispersant.
[0014] The fifth aspect of the present invention relates to a coating film forming composition for a viewing angle improving optical film, comprising the spherical alumina particle dispersion for a viewing angle improving optical film and a coating film forming component. In an embodiment of the present invention, alcohols may be included.
[0015] A sixth aspect of the present invention relates to a viewing angle-improving optical film which is a cured film of the coating film-forming composition for a viewing angle-improving optical film.
[0016] The viewing angle improving optical film according to the embodiment of the present invention has a ratio (900 nm / 350 nm) of white light transmittance at a wavelength of 900 nm to that at a wavelength of 350 nm of less than 3.10; The cured film may have a transmitted light intensity of 2900 or more when the incident angle of white light with respect to the surface of the cured film is 0°, and a transmitted light intensity of 430 or more when the incident angle is 5°. Effect of the Invention
[0017] According to the present invention, it is possible to provide a technique for improving the viewing angle characteristics of a light scattering layer provided on the surface of a liquid crystal panel. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is a diagram showing an electron microscope image of alumina particles contained in the alumina particle dispersion obtained in Example 1. [Diagram 2] FIG. 2 is a diagram showing an electron microscope image of alumina particles contained in an alumina particle dispersion obtained in Comparative Example 1. [Diagram 3] FIG. 2 is a diagram showing an electron microscope image of alumina particles contained in an alumina particle dispersion obtained in Comparative Example 2. [Figure 4] FIG. 13 is a diagram showing an electron microscope image of alumina particles contained in an alumina particle dispersion obtained in Comparative Example 3. [Diagram 5] FIG. 13 is a diagram showing an electron microscope image of alumina particles contained in an alumina particle dispersion obtained in Comparative Example 4. [Figure 6] FIG. 2 is a graph showing the spectra of white light transmitted through the cured films of Example 1 and Comparative Examples 1 to 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The method for producing a spherical alumina particle dispersion according to an embodiment of the present invention is a method for producing a spherical alumina particle dispersion containing spherical alumina particles, a dispersant, and a solvent. This production method includes a step of dispersing raw alumina particles, which are the raw material of the spherical alumina particles, a liquid containing a dispersant containing at least one selected from a nonionic dispersant and a cationic dispersant, and a solvent (hereinafter referred to as a "raw material liquid") together with beads having an average particle diameter of less than 0.10 mm, to disperse the raw material alumina particles so that the spherical alumina particles are substantially composed of spherical alumina particles having an average particle diameter of 1 to 10 μm.
[0020] The raw alumina particles are not particularly limited, and conventionally known alumina particles can be used, and commercially available ones can be used. The alumina particles may be those containing alumina as a main component, and may contain other components. They may also be surface-treated. The shape of the raw alumina is not particularly limited, but from the viewpoint of the efficiency of producing spherical alumina particles, spherical alumina particles are preferred. The average particle size of the spherical alumina particles as the raw alumina particles is preferably 1 to 10 μm.
[0021] The content of the raw material alumina particles is preferably 25.0 to 70.0% by weight, more preferably 25.0 to 65.0%, based on the total amount of the raw material liquid.
[0022] The dispersant may be at least one selected from nonionic dispersants and cationic dispersants, and examples of the dispersant include those containing only a nonionic dispersant as an active ingredient, those containing only a cationic dispersant as an active ingredient, and those containing a nonionic dispersant and a cationic dispersant as an active ingredient. Of these, it is preferable to use those containing a nonionic dispersant and a cationic dispersant as active ingredients, that is, a nonionic dispersant and a cationic dispersant. In particular, when these two types of dispersants are used, the obtained spherical alumina particles tend to be more uniformly dispersed in the dispersion and the coating film-forming composition. The reason for this is not necessarily clear, but it is presumed that the aggregation of alumina particles is more effectively suppressed from the viewpoint that (a) the nonionic dispersant has a weak adsorption force to alumina particles, (b) the cationic dispersant has an excessively strong adsorption force to alumina particles, and (c) when both are used in combination, the nonionic dispersant is thought to have entered between the cationic dispersants adsorbed to the alumina particles.
[0023] The nonionic dispersant is not particularly limited, and known dispersants can be used. For example, a polymeric compound having a polyoxyethylene chain can be mentioned. Examples of polymeric compounds having a polyoxyethylene chain include alkyl polyoxyethylene ethers, alkyl polyoxyethylene-polyoxypropylene ethers, alkyl polyoxypropylene-polyoxyethylene ethers, polyoxyethylene-polyoxypropylene ethers (polyoxyethylene oxypropylene block copolymers), fatty acid polyoxyethylene esters, fatty acid polyoxyethylene sorbitan esters, fatty acid polyoxyethylene sorbitol esters, polyoxyethylene sorbitan monoalkyl ethers, polyoxyethylene alkyl ether sulfates, polyoxyethylene castor oil (hydrogenated castor oil), and acetylene glycol ethylene oxide adducts. Examples of alkyl polyoxyethylene ethers include polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene oleyl ether, polyoxyethylene octyl ether, polyoxyethylene cetyl ether, polyoxyethylene octyl phenyl ether, and polyoxyethylene nonyl phenyl ether. An example of the fatty acid polyoxyethylene sorbitan ester is polyoxyethylene sorbitan monolaurate.
[0024] The cationic dispersant is not particularly limited, and known dispersants can be used. Examples include alkylamine salts, acylamine salts, quaternary ammonium salts, ammonium salts having an amide bond, an ester bond, or an ether bond, imidazoline, imidazolium salts, and amine derivatives. The cationic dispersant may be a low molecular weight compound or a high molecular weight compound, but from the viewpoint of the dispersibility of alumina particles, high molecular weight compounds are preferred. Examples of such high molecular weight dispersants include polyethyleneimine, aminoalkyl (meth)acrylate copolymers, polyvinylimidazoline, polyvinylpyridine derivatives, polyoxyethylene alkylamines, and polyoxyethylene alkylamides. Examples of polyvinylpyridine derivatives include copolymers of vinylpyridine and (meth)acrylic acid, and copolymers of vinylpyridine, (meth)acrylic acid, and oxyethylene group-containing high molecular weight compounds. Examples of copolymers of vinylpyridine, (meth)acrylic acid, and oxyethylene group-containing high molecular weight compounds include copolymers of vinylpyridine, (meth)acrylic acid, and polyoxyethylene. Among these, from the viewpoint of the dispersibility of alumina particles, amine high molecular weight dispersants are preferred.
[0025] The combination of the nonionic dispersant and the cationic dispersant can be selected in consideration of the relationship with other components, but both are preferably polymeric dispersants, and it is more preferable that the blocks constituting the polymer compounds of both of them contain common structural units. For example, it is even more preferable that both dispersants have polyoxyethylene chains.
[0026] The contents of the nonionic dispersant and the cationic dispersant are not particularly limited, and can be selected in consideration of the relationship with other components. The nonionic dispersant is preferably 0.75 to 6.0% by weight (based on solids (non-volatile content)) in the total amount of the raw material liquid. The cationic dispersant is preferably 0.7 to 5.0% by weight (based on solids (non-volatile content)) in the total amount of the raw material liquid. The mixing ratio of the two is also not particularly limited, and can be selected in consideration of the characteristics of both dispersants and the relationship with other components. From the viewpoint of the dispersibility of alumina particles, it is preferable that the blending ratio of both components contains more nonionic.
[0027] The solvent may be appropriately selected depending on the type of coating film-forming components described below, and examples thereof include various organic solvents such as aromatic hydrocarbons, aliphatic hydrocarbons, ketones, esters, glycol ethers, and alcohols, water, etc. Of these, water is particularly preferred from the viewpoint of environmental friendliness.
[0028] The content (addition amount) of the solvent is preferably 20 to 40% by weight based on the total amount of the raw material liquid.
[0029] The raw material liquid may contain other components as necessary, such as an antifoaming agent.
[0030] The defoaming agent can be used for the purpose of suppressing and breaking foam when foaming occurs during dispersion treatment. Examples of such defoaming agents include silicone-based, surfactant-based, and mineral oil-based agents. The form of the silicone-based defoaming agent is not particularly limited, and examples include (a) an O / W emulsion type in which silicone oil and silica fine particles are emulsified with, for example, a nonionic surfactant, (b) an oil type composed of silicone oil, (c) a solution type in which silicone oil is dissolved in a hydrocarbon solvent, and (d) a mixture of foam-breaking polysiloxane, hydrophobic particles, and polyglycol. The content of the defoaming agent is not particularly limited, and can be, for example, 0.001 to 0.1 parts by weight (based on solids (non-volatile content)) per 100 parts by weight of spherical alumina particles.
[0031] The average particle size of the beads used in the dispersion treatment is less than 0.10 mm. From the viewpoint of dispersing the alumina particles while maintaining their spherical shape, i.e., preventing Rayleigh scattering, the average particle size is preferably 0.08 mm or less, more preferably 0.06 mm or less, and even more preferably 0.05 mm or less. From the viewpoint of not crushing the alumina particles and not causing Rayleigh scattering, the average particle size is preferably 0.05 mm or less.
[0032] The material of the beads is not particularly limited, and known materials can be used. For example, zirconia, alumina, zircon, glass, etc. are listed. In the case of a batch type, the amount of beads added is adjusted so that the beads are preferably 40 to 80 volume % and more preferably 50 to 70 volume % relative to the volume of the mill base in the mill. In the case of a circulation type, the amount is adjusted so that the beads are preferably 40 to 80 volume % and more preferably 50 to 70 volume % relative to the volume of the mill.
[0033] In the method for producing a spherical alumina particle dispersion according to the embodiment, the above-mentioned components are mixed to prepare a raw material liquid, and the above-mentioned beads are present in the raw material liquid to carry out a dispersion treatment. The dispersion treatment can be carried out using a bead mill, a mass colloider, a ball mill, a sand mill, or the like. There are no particular limitations on the conditions for the dispersion treatment, and for example, in the case of a sand mill, it is preferable to carry out the dispersion treatment at 25 to 40°C and 1500 rpm to 2000 rpm for 1 to 2 hours.
[0034] After the dispersion treatment, the beads are removed as necessary. The beads can be removed by filtration or the like. Also, the above-mentioned solvent can be added before or after removing the beads as necessary. The solvent to be added is not particularly limited, but it is preferable to use the same solvent as that used during the dispersion treatment. Also, the amount of solvent to be added can be appropriately determined, but for example, it can be added so that the solid content is 30 to 60% by weight. In this way, a spherical alumina particle dispersion can be obtained.
[0035] In the spherical alumina particle dispersion obtained as described above, the raw alumina particles are prevented from being broken down to generate alumina particles of an irregular shape, and spherical alumina particles substantially composed of spherical particles are present, so that Rayleigh scattering caused by alumina particles of an irregular shape is suppressed in the coating film described below. In addition, by using the above-mentioned dispersant, particularly the two predetermined dispersants, it is possible to uniformly disperse spherical alumina particles substantially composed of spherical particles having an average particle size in a predetermined range in the coating film, so that the light scattering effect of the spherical alumina particles is good and the effect of increasing the viewing angle can be imparted. Therefore, such a spherical alumina particle dispersion is suitable, for example, for a viewing angle improving optical film. And, when such a spherical alumina particle dispersion is used to form a cured film as described below, Rayleigh scattering is suppressed, and for example, the ratio of the transmittance of white light at a wavelength of 900 nm to that at a wavelength of 350 nm (900 nm / 350 nm) is less than 3.10.
[0036] The average particle size of the spherical alumina particles is 1 to 10 μm from the viewpoint of improving the viewing angle. It is preferably 1 to 4 μm. The average particle size can be measured, for example, by a laser diffraction / scattering type particle size distribution measuring device (LA-950 type, manufactured by Horiba, Ltd.). As described above, the spherical alumina particles contained in the dispersion are substantially composed of spherical alumina particles having an average particle size within a predetermined range. Here, the term "spherical alumina particles" does not mean to be limited to particles that are truly spherical, but means that alumina particles having an irregular shape such as a defective shape are not included as a result of the dispersion treatment using beads. "Substantially" does not mean that such alumina particles having an irregular shape are not included at all, but allows them to be included to an extent that Rayleigh scattering, which will be described later, can be prevented.
[0037] Next, a method for producing a coating forming composition according to an embodiment of the present invention will be described. In this embodiment, the coating forming composition is produced using the spherical alumina particle dispersion obtained as described above. In other words, the method for producing the spherical alumina particle dispersion described above corresponds to the spherical alumina particle dispersion preparation step in the coating forming composition production method. Then, a coating forming composition preparation step is performed in which a coating forming component is added to the spherical alumina particle dispersion obtained in this step and the mixture is stirred.
[0038] Examples of the coating film forming component include resins capable of forming a transparent cured film. Examples of such resins include cellulose acetate-based resins such as triacetyl cellulose, (meth)acrylic resins such as polymethyl methacrylate and polyacrylate, (meth)acrylic acid alkyl-styrene copolymers, vinyl chloride-based resins, polycarbonate-based resins, polyester-based resins such as polyethylene terephthalate, polyolefin-based resins such as polyethylene, polypropylene, and polynorbornene, polystyrene resins, silicone resins, epoxy resins, and melamine resins. In addition, in order to increase the degree of curing of the resin coating for the purpose of improving abrasion resistance, heat resistance, and adhesion to the substrate, a curing agent suitable for the above-mentioned various resins may be used.
[0039] The content of the coating film forming component is preferably 120 to 280 parts by weight (based on the solid content (non-volatile content)) per 100 parts by weight of the spherical alumina particles in the spherical alumina particle dispersion.
[0040] The stirring treatment is not particularly limited, and can be performed, for example, by using a disper, a shaker, etc. The stirring temperature and time can be appropriately determined depending on the component composition.
[0041] During the stirring process, a solvent may be added as necessary. The solvent used in preparing the spherical alumina particle dispersion may be used. The solvent to be added may be appropriately selected according to the solvent contained in the spherical alumina particle dispersion. For example, when the spherical alumina particle dispersion does not contain alcohols or ketones, it is preferable to add a solvent having a lower surface tension than the solvent used in order to further improve the smoothness of the coating film or cured film described later. The solvent to be added is preferably alcohols, ethers, or ketones. From the viewpoint of film-forming properties, alcohols having a boiling point of 25 to 83°C are preferable. Examples of such alcohols include monohydric alcohols and glycols having 1 to 3 carbon atoms, but it is necessary to dissolve the solvent contained in the spherical alumina particle dispersion or to be compatible with the solvent contained in the spherical alumina particle dispersion. For example, when water is used as a solvent in preparing the spherical alumina particle dispersion and a coating film-forming composition is prepared, it is preferable to add the above-mentioned alcohols. The content of the solvent added is preferably 0.1 to 5.0% by weight in the coating film forming composition.
[0042] The coating film-forming composition thus obtained contains the above-mentioned alumina particle dispersion, so that the predetermined alumina particles and the coating film-forming components are uniformly dispersed, and it is possible to form a coating film in which the predetermined alumina particles are uniformly dispersed. Therefore, the coating film-forming composition has a good light scattering effect due to the spherical alumina particles, and it is possible to increase the viewing angle of the cured film. When alcohols are contained, the viewing angle can be further increased. Therefore, the coating film-forming composition is suitable for, for example, a viewing angle improving optical film.
[0043] Next, a method for producing a cured film according to an embodiment of the present invention will be described. In this embodiment, a cured film is produced using the film-forming composition obtained as described above. That is, the spherical alumina particle dispersion preparation step and the film-forming composition preparation step in the method for producing a cured film are common to the method for producing a film-forming composition. In the method for producing a cured film, the film-forming composition obtained in the film-forming composition preparation step is applied to a substrate surface to form a coating film, which is then cured to form a cured film (cured film formation step).
[0044] The substrate that can be used is not particularly limited as long as it is transparent. Examples of materials constituting the substrate include quartz glass, soda glass, polycarbonate, polymethyl methacrylate, polyvinyl chloride, polyester, cellulose acetate butyrate, polyolefin, polystyrene, epoxy resin, polyacrylate, silicone resin, transparent fluororesin, polyethylene terephthalate, cycloolefin polymer, polyimide, etc.
[0045] The shape of the substrate is not particularly limited, and may be, for example, a film. When the substrate is a film, the thickness may be, for example, 10 to 3000 μm. When forming an optical film as an optical member, the thickness may be, for example, 10 to 300 μm.
[0046] The coating film-forming composition can be applied to the surface of a substrate by a conventional method, such as reverse roll coating, die coating, comma coater, die coater, spray coating, gravure coating, rod coating, brush coating, roller coating, spray coating, cationic electrodeposition coating, electrostatic coating, etc.
[0047] The coating thickness is preferably 1 to 500 μm, more preferably 1 to 200 μm, in a dry state, and can be, for example, 1 to 100 μm for optical film applications.
[0048] The curing conditions can be appropriately determined depending on the coating film-forming components, etc.
[0049] The cured film obtained as described above is formed using the coating film-forming composition described above, so that it is possible to form a coating film (before curing) in which the specified alumina particles are uniformly dispersed. Therefore, the specified alumina particles are also uniformly dispersed in the obtained cured film. Therefore, the cured film has a good light scattering effect due to the spherical alumina particles, and the viewing angle is greatly improved. Therefore, the cured film is suitable, for example, as a viewing angle improving optical film. In addition, by adding alcohols to the coating film-forming composition, it is possible to further improve the light scattering effect and viewing angle characteristics of the obtained cured film, so that the coating film-forming composition is more suitable for use as a viewing angle improving optical film, and the cured film is more suitable as a viewing angle improving optical film. In addition, since the alumina particles have excellent heat dissipation properties, the heat dissipation effect due to the uniformly dispersed specified alumina particles can also be expected. Therefore, the cured film is also suitable as a heat dissipation material. In addition, since the alumina particles have excellent heat dissipation properties, the heat dissipation effect due to the uniformly dispersed specified alumina particles can also be expected. Therefore, the cured film is also suitable as a heat dissipation material.
[0050] In addition, when the cured film is applied as a viewing angle improving optical film, from the viewpoint of suppressing Rayleigh scattering, the ratio of the transmittance of white light at a wavelength of 900 nm to that at a wavelength of 350 nm (900 nm / 350 nm) is preferably less than 3.10, more preferably 3.00 or less, even more preferably 2.50 or less, and particularly preferably 2.00 or less. In addition, from the viewpoint of the viewing angle, the transmitted light intensity of white light at an incident angle of 0° to the surface of the cured film is preferably 2900 or more, and the transmitted light intensity of white light at an incident angle of 5° is preferably 430 or more, more preferably 550 or more. These transmittances and transmitted light intensities of white light can be measured, for example, by the method described later. Furthermore, for example, in a cured film obtained using a coating film-forming composition containing alcohols, the ratio of the transmitted light intensity of white light at an incident angle of 0° to the transmitted light intensity of white light at an incident angle of 5° or -5° can both be closer to 1, compared to a cured film not containing alcohols, i.e., the viewing angle characteristics can be further improved. EXAMPLES
[0051] Hereinafter, the embodiment of the present invention will be described in detail based on examples.
[0052] (Example 1, Comparative Examples 1 to 4) <Production of alumina particle dispersion (alumina particle dispersion preparation step)> Raw material alumina particles (manufactured by Denka Co., Ltd., DAW-0105, spherical shape, average particle diameter: 2 μm): 120.00 g (solid content), nonionic dispersant (manufactured by BYK-Chemie, DISPERBYK-193, polymer compound having polyoxyethylene chain, solid content 40.3%): 23.16 g, cationic dispersant (manufactured by BASF, Efka PX4701, acrylic-vinylpyridine copolymer having polyoxyethylene chain, solid content 100%): 5.07 g, silicone-based defoamer (manufactured by BYK-Chemie, BYK-024, solid content 100%): 0.10 g, and solvent (pure water): 51.67 g were mixed and pre-dispersed to prepare a raw material liquid. 366.66 g (60 volume % based on the mill base volume of the mill) of zirconia beads having the average particle size shown in Table 1 was added to the raw material liquid, and dispersion treatment was carried out at 25°C for 80 minutes using a batch sand mill with a peripheral speed of 4.24 m / s. Thereafter, 40.00 g of pure water was added, and filtration was performed to remove the zirconia beads, thereby obtaining an alumina particle dispersion. In addition, in the "composition of the cured film" in Table 1, the components other than the acrylic resin have the same composition ratio in the solid content of the alumina particle dispersion.
[0053] <Production of the film-forming composition (film-forming composition preparation step)> 30.00 g of the obtained alumina particle dispersion and 104.47 g of a coating film forming component (Vinibran (registered trademark) 717L, acrylic resin, solid content 23.3%, manufactured by Nissin Chemical Industry Co., Ltd.) were mixed, and pure water was added so that the solid content concentration was 30% by weight, followed by stirring to obtain a coating film forming composition.
[0054] <Production of cured film (cured film formation process)> The obtained coating film-forming composition was applied to a polyethylene terephthalate film (Cosmoshine (registered trademark) A4100, manufactured by Toyobo Co., Ltd.) using a bar coater so as to give a wet film thickness of 37.5 μm, and dried at 60° C. for 15 minutes to form a cured film. The obtained cured film was used for the evaluations described below.
[0055] (evaluation) <Measurement of the average particle size of alumina particles> The average particle size of the alumina particles in the obtained alumina particle dispersion was measured using a laser diffraction / scattering type particle size distribution measuring device (LA-950, manufactured by Horiba, Ltd.).
[0056] <Observation of the appearance of alumina particles> 0.2 g of the obtained alumina particle dispersion and 1.0 g of distilled water were added to an aluminum container and stirred, then heated at 130°C for 16 hours to dry, to obtain a sample for observation. The obtained observation material was observed using an electron microscope (Thermoscinetific, Phenom ProX). The measurement conditions were a magnification of 5000 times and a measurement mode of an accelerating voltage of 15 kV / mapping mode. The images are shown in Figures 1 to 5.
[0057] <Rayleigh scattering evaluation (white light transmittance)> The spectrum of transmitted light was measured using the obtained cured film with an ultraviolet-visible-near infrared spectrophotometer (V-670 UV / Vis / NIR Spectrophotometer, manufactured by JASCO Corporation), and the ratio of the transmittance of white light at a wavelength of 900 nm to that at a wavelength of 350 nm (900 nm / 350 nm) was calculated. A ratio of less than 3.10 was evaluated as having suppressed Rayleigh scattering. The evaluation results are shown in Table 1. The spectrum of transmitted light is shown in Figure 6.
[0058] [Table 1]
[0059] (Examples 2 and 3, Comparative Example 5) A spherical alumina particle dispersion, a coating film-forming composition, and a cured film were prepared in the same manner as in Example 1, except that the zirconia beads used to disperse the raw material liquid were the same as those in Example 1, and the type and content of the dispersant used were as shown in Table 2. The obtained cured film was used to evaluate the viewing angle. It was confirmed that the average particle size and outer diameter of the alumina particles in the alumina particle dispersion obtained in Examples 2 and 3 were equivalent to those in Example 1. In addition, the above-mentioned Rayleigh scattering evaluation results performed using the cured films obtained in Examples 2 and 3 confirmed that the predetermined ratio was less than 3.10. In the "composition of the cured film" in Table 2, the components other than the acrylic resin have the same composition ratio in the solid content of the alumina particle dispersion. In addition, SN Dispersant 5468 (solid content 41%) manufactured by San Nopco Ltd. was used as the anionic dispersant.
[0060] <Viewing angle evaluation> Using GENESIA Gonio manufactured by Genesia Co., Ltd., the transmitted light intensity of white light at an incident angle of 0° to the surface of the cured film obtained in Example 1 and Comparative Examples 5 to 7 and the transmitted light intensity of white light at the incident angle of 5° were measured. The evaluation criteria were as follows: a good viewing angle was obtained when the transmitted light intensity of white light at an incident angle of 0° to the surface of the cured film was 2900 or more, and a good viewing angle was obtained when the transmitted light intensity of white light at an incident angle of 5° was 430 or more, and a better viewing angle was obtained when the transmitted light intensity was 550 or more. The value of the incident angle of 5° was required to be equal to or greater than a predetermined value, among the transmitted light intensities at incident angles of ±5°.
[0061] The product configuration and conditions of GENESIA Gonio, manufactured by Genesia Co., Ltd., are as follows. 1. Measuring machine GENESIA Gonio / Far Field Profiler 1-2.Light source White light source: White LED manufactured by Nichia Corporation (model number NSPW300BS) Detector Detector: Hamamatsu Photonics, Si photodiode (model number S2386-5K) 1-4. Measurement conditions Transmission scattering measurement
[0062] [Table 2]
[0063] As shown in Table 1, when the average particle diameter of the beads used in preparing the alumina particle dispersion is less than 0.10 mm, the ratio of the transmittance of white light at wavelengths of 900 nm and 350 nm (900 nm / 350 nm) is less than 3.10, and it is understood that Rayleigh scattering is suppressed. This point can also be understood from FIG. 6 (spectrum from wavelengths of 350 mm to 900 mm). As shown in FIG. 6, in Comparative Examples 1 to 4, an increase in transmittance at long wavelengths and a decrease in transmittance at short wavelengths are observed due to Rayleigh scattering caused by amorphous alumina particles (crushed material), but in Example 1, it is understood that these are suppressed more than in the comparative example. In addition, as can be seen in the area surrounded by the white line in Comparative Example 1 in FIG. 2, amorphous alumina particles are clearly present in Comparative Examples 2 to 4 in FIGS. 3 to 5, while in Example 1 in FIG. 1, amorphous alumina particles are hardly observed, and it can be seen that the spherical alumina particles are substantially composed of spherical alumina particles. Furthermore, as shown in Table 2, by using a spherical alumina particle dispersion prepared using specified beads and a specific dispersant, the cured film obtained has a transmitted light intensity of white light equal to or greater than a specified value, regardless of whether the incident angle is 0° or ±5°, and the viewing angle is improved.
[0064] Example 4 <Production of spherical alumina particle dispersion (spherical alumina particle dispersion preparation step)> A spherical alumina particle dispersion was obtained in the same manner as in Example 1.
[0065] <Production of the film-forming composition (film-forming composition preparation step)> 30.00 g of the obtained spherical alumina particle dispersion, 104.47 g of a coating film forming component (Vinyblan (registered trademark) 717L, acrylic resin, solid content 23.3%, manufactured by Nissin Chemical Industry Co., Ltd.), and 1.39 g of alcohol (isopropyl alcohol (IPA) manufactured by Sagane Bussan Co., Ltd.) were mixed, and pure water was added so that the solid content concentration was 29.70% by weight, followed by stirring to obtain a coating film forming composition.
[0066] <Production of cured film (cured film formation process)> A cured film was formed in the same manner as in Example 1. The obtained cured film was used to evaluate the viewing angle as described above. The evaluation results are shown in Table 3.
[0067] Example 5 A cured film was obtained in the same manner as in Example 4, except that in the production of the coating-forming composition (coating-forming composition preparation step), methanol (MeOH) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used instead of IPA as the alcohol. The evaluation results are shown in Table 3.
[0068] Example 6 A cured film was obtained in the same manner as in Example 4, except that in the production of the coating-forming composition (coating-forming composition preparation step), ethanol (EtOH) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used instead of IPA as the alcohol. The evaluation results are shown in Table 3.
[0069] [Table 3]
[0070] As shown in Table 3, by adding alcohols when preparing the coating film-forming composition, each value increases and light scattering is improved compared to when no alcohols are added (Example 1), and the ratio of 0° to +5° or -5° approaches 1, indicating that the viewing angle characteristics are improved. In other words, it is understood that the alcohols improve the function of the cured film as a light scattering film. This is presumably because the alcohols improve the smoothness of the coating film, which in turn improves the smoothness of the surface of the cured film.
Claims
1. A method for producing a spherical alumina particle dispersion comprising spherical alumina particles, a dispersant, and a solvent, comprising the steps of: The method includes a step of dispersing raw alumina particles, which are raw materials for the spherical alumina particles, a liquid containing a dispersant containing at least one selected from a nonionic dispersant and a cationic dispersant, and a solvent, together with beads having an average particle diameter of less than 0.10 mm, to disperse the raw alumina particles so that the spherical alumina particles are substantially composed of spherical alumina particles having an average particle diameter of 1 to 10 μm; The average particle size of the spherical alumina particles is measured by a laser diffraction / scattering type particle size distribution measuring device, The spherical alumina particles means that the alumina particles do not contain alumina particles having an irregular shape due to defects as a result of the dispersion treatment, in this method for producing a spherical alumina particle dispersion.
2. 2. The method for producing a spherical alumina particle dispersion according to claim 1, wherein the dispersant comprises a nonionic dispersant and a cationic dispersant.
3. 3. The method for producing a spherical alumina particle dispersion according to claim 2, wherein the cationic dispersant is an amine-type polymer dispersant.
4. 4. The method for producing a spherical alumina particle dispersion according to claim 1, wherein the average particle size of the raw material alumina particles is 1 to 10 μm.
5. a spherical alumina particle dispersion preparation step in which a liquid containing raw alumina particles as the raw material for the spherical alumina particles, a dispersant containing at least one selected from a nonionic dispersant and a cationic dispersant, and a solvent is subjected to a dispersion treatment together with beads having an average particle diameter of less than 0.10 mm to disperse the raw alumina particles so that the spherical alumina particles are substantially composed of spherical alumina particles having an average particle diameter of 1 to 10 μm; a coating film-forming composition preparation step of adding a coating film-forming component to the spherical alumina particle dispersion obtained in the spherical alumina particle dispersion preparation step and stirring the mixture; Including, The average particle size of the spherical alumina particles is measured by a laser diffraction / scattering type particle size distribution measuring device, The method for producing a coating forming composition, wherein the spherical alumina particles means that the dispersion treatment does not include alumina particles having an irregular shape due to defects.
6. a spherical alumina particle dispersion preparation step in which a liquid containing raw alumina particles as the raw material for the spherical alumina particles, a dispersant containing at least one selected from a nonionic dispersant and a cationic dispersant, and a solvent is subjected to a dispersion treatment together with beads having an average particle diameter of less than 0.10 mm to disperse the raw alumina particles so that the spherical alumina particles are substantially composed of spherical alumina particles having an average particle diameter of 1 to 10 μm; a coating film-forming composition preparation step of adding and mixing a coating film-forming component to the spherical alumina particle dispersion obtained in the spherical alumina particle dispersion preparation step; a cured film-forming step of applying the coating film-forming composition obtained in the coating film-forming composition preparation step to a substrate surface to form a coating film, and curing the coating film to form a cured film; Including, The average particle size of the spherical alumina particles is measured by a laser diffraction / scattering type particle size distribution measuring device, The spherical alumina particles means that the alumina particles do not contain alumina particles having an irregular shape due to defects as a result of the dispersion treatment, in the method for producing a cured film.
7. The method for producing a cured film according to claim 6 , wherein the cured film is for use in a viewing angle improving optical film.
8. The composition comprises spherical alumina particles substantially composed of spherical alumina particles having an average particle size of 1 to 10 μm, a dispersant containing at least one selected from a nonionic dispersant and a cationic dispersant, and a solvent, The average particle size of the spherical alumina particles is measured by a laser diffraction / scattering type particle size distribution measuring device, The spherical alumina particles mean that the spherical alumina particle dispersion for a viewing angle improving optical film does not contain alumina particles having an irregular shape including defects.
9. 9. The spherical alumina particle dispersion for a viewing angle improving optical film according to claim 8, wherein the dispersant comprises a nonionic dispersant and a cationic dispersant.
10. A coating-forming composition for a viewing angle-improving optical film, comprising the spherical alumina particle dispersion for a viewing angle-improving optical film according to claim 8 or 9 and a coating-forming component.
11. The coating composition for a viewing angle improving optical film according to claim 10, which comprises an alcohol.
12. A viewing angle-improving optical film which is a cured film of the coating film-forming composition for a viewing angle-improving optical film according to claim 10 or 11.
13. The ratio of the transmittance of white light at a wavelength of 900 nm to that at a wavelength of 350 nm (900 nm / 350 nm) is less than 3.10; the transmitted light intensity of white light at an incident angle of 0° to the surface of the cured film is 2900 or more, and the transmitted light intensity of white light at an incident angle of 5° to the surface of the cured film is 430 or more; The viewing angle improving optical film according to claim 12.
Citation Information
Patent Citations
Scratch-resistant and wear-resistant composition and preparation method and application thereof
CN102827500A
Manufacture of optical diffusion panel
JP1996146525A
Color filter substrate for transflective liquid crystal display device, method for manufacturing the same, and transflective liquid crystal display device
JP2011154327A
Transmission type liquid crystal display device
WO2010143552A1